1988
DOI: 10.1084/jem.168.3.1061
|View full text |Cite
|
Sign up to set email alerts
|

Early events in human T cell ontogeny. Phenotypic characterization and immunohistologic localization of T cell precursors in early human fetal tissues.

Abstract: During early fetal development, T cell precursors home from fetal yolk sac and liver to the epithelial thymic rudiment. From cells that initially colonize the thymus arise mature T cells that populate T cell zones of the peripheral lymphoid system. Whereas colonization of the thymus occurs late in the final third of gestation in the mouse, in birds and humans the thymus is colonized by hematopoietic stem cell precursors during the first third of gestation. Using a large series of early human fetal tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(106 citation statements)
references
References 52 publications
7
96
1
2
Order By: Relevance
“…The fist hematopoietic cells begin to appear in the human fetal thymus at eight to nine weeks gestation. The first appearance of single-positive reactive T lymphocytes in the fetal thymus occurs around 13-14 weeks gestation, and these cells appear in the circulation (post-thymic) at 15-16 weeks gestation [60,61]. Therefore, appropriately timed transplantation of pluripotent, immortal HSCs should theoretically result in permanent, multilineage, hematopoietic chimerism without the need for immunosuppression or marrow ablation.…”
Section: Induction Of Tolerancementioning
confidence: 99%
“…The fist hematopoietic cells begin to appear in the human fetal thymus at eight to nine weeks gestation. The first appearance of single-positive reactive T lymphocytes in the fetal thymus occurs around 13-14 weeks gestation, and these cells appear in the circulation (post-thymic) at 15-16 weeks gestation [60,61]. Therefore, appropriately timed transplantation of pluripotent, immortal HSCs should theoretically result in permanent, multilineage, hematopoietic chimerism without the need for immunosuppression or marrow ablation.…”
Section: Induction Of Tolerancementioning
confidence: 99%
“…We are currently using B7 + cell transfectants to address this issue further. While a ligand for CD7 has not been identified, CD7 is one of the earliest T cell-specific markers in the thymus (29,30). Its absence has been reported in one case of severe combined immunodeficiency (31), and CD7 mAb crosslinking has been reported to induce changes in intracellular Ca 2+ (15), as well as enhancing T cell proliferation (14).…”
Section: Regulation Of Differential Naive and Memory T Cell Adhesion mentioning
confidence: 99%
“…Among human thymocytes, CD7 + CD2 -CD3 -CD4 -CD8 -(referred hereafter as CD7') cells represent the earliest identifiable step (2)(3)(4) . In vitro, these precursors were able to acquire mature T cell antigens (3,4), but cellular interactions and cytokines necessary for this process are poorly understood. We have previously reported that enriched populations of B lymphocytes from blood produce factors (3,5) that promote in vitro development of blood-and bone marrow-derived CD7 + CD2 -precursors.…”
mentioning
confidence: 99%